V. V. Mayakovsky in the Literary Heritage of Hrachya Tamrazyan - KHANJYAN, NATALYA (Bulletin of Yerevan University H: Russian Philology, 2021)
The author presents H.Tamrazyan as a distinguished scientist (medievalist) and poet, as well as outstanding translator of Russian poetry into Armenian language. Tamrazyan’s works, editions as a translator of V. Mayakovsky’s, S.Yesenin’s, B.Pasternak’s verses are the subject of special attention. Besides, the author translates and publishes in Russian Tamrazyan’s essay “Early Mayakovsky” (1996), with comments on it.